DEFINITION AND CLASSIFICATION OF SOCIAL MEDIA PLATFORMS IN LANGUAGE EDUCATION (SCIENCE TIME JOURNAL, 2026)
The rapid development of digital technologies has significantly transformed language education, particularly through the integration of social media platforms. Social media has evolved from being merely a communication tool to an influential educational environment that supports collaborative learning, authentic language exposure, and learner autonomy. This article explores the definition and classification of social media platforms within the context of language education. It examines various types of platforms—such as social networking sites, content-sharing platforms, microblogging tools, messaging applications, and educational communities—and analyzes their pedagogical potential in developing linguistic skills. Special attention is paid to how these platforms enhance interaction, intercultural competence, motivation, and real-life language use. The study highlights the role of social media as a supplementary instructional tool that fosters communicative competence and digital literacy in foreign language learning.